2017
DOI: 10.3389/fnagi.2017.00161
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Gray Matter Volume in Patients with Type 2 Diabetes Mellitus

Abstract: Background and Purpose: Previous studies of voxel-based morphometry (VBM) have found that patients with type 2 diabetes mellitus (T2DM) exhibit gray matter alterations, but these findings are inconsistent and have not been quantitatively reviewed. Therefore, the aim of this study was to conduct a quantitative meta-analysis of VBM studies of patients with T2DM.Materials and Methods: The seed-based d mapping method was applied to quantitatively estimate the regional gray matter abnormalities in T2DM patients. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
36
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 41 publications
9
36
1
Order By: Relevance
“…The finding on brain tissue density change is consistent with previous studies that showed reduced regional gray matter in brain sites such as prefrontal cortex, medial temporal, anterior cingulate, and medical frontal lobes, and hippocampal region in T2DM patients as compared with non-T2DM control subjects. 18,20,31 Etiology of the brain damage specifically occurring in prefrontal cortices in T2DM is not fully understood. However, diabetic vasculopathy (arterial stiffness, atherosclerosis, and endothelial dysfunction) and oxidative stress are believed to be important potential underlying mechanisms of T2DM-induced brain injury by causing neuroinflammation, neurodegeneration, and neuronal apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…The finding on brain tissue density change is consistent with previous studies that showed reduced regional gray matter in brain sites such as prefrontal cortex, medial temporal, anterior cingulate, and medical frontal lobes, and hippocampal region in T2DM patients as compared with non-T2DM control subjects. 18,20,31 Etiology of the brain damage specifically occurring in prefrontal cortices in T2DM is not fully understood. However, diabetic vasculopathy (arterial stiffness, atherosclerosis, and endothelial dysfunction) and oxidative stress are believed to be important potential underlying mechanisms of T2DM-induced brain injury by causing neuroinflammation, neurodegeneration, and neuronal apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…The checklist was made in accordance with the studies published before (12,19). The contents of the checklist were included in the Table S1.…”
Section: Quality Assessmentmentioning
confidence: 99%
“…The DMN is involved in cognitive functions such as episodic memory retrieval, self-referencing, and emotion management (Buckner et al, 2008). Previous studies have found decreased gray-matter volume in DMN-related regions (Liu et al, 2017), and abnormal FC within the DMN as well as between the DMN and other brain regions (including the cerebellum) in patients with T2DM (Zhou et al, 2010;Musen et al, 2012;Zhang et al, 2015;Yang et al, 2016). The present study provides further evidence for the impairment of the cerebellumcerebral DMN connection in patients with T2DM, especially a disconnection between the bilateral cerebellar region IX and the right cuneus/precuneus.…”
Section: Decreased Connectivity Of the Cerebellum-cerebral Dmn In T2dmmentioning
confidence: 99%